Blended Learning Strategies of Telegram-Assisted Learning Towards Student Mathematics Learning Results Reviewed from Learning Style - Suryati, Kadek; Adnyana, I Gede (Universitas Muhammadiyah Mataram, 2020)
The research aims to describe the influence of telegram-assisted blended learning strategies on mathematics learning outcomes in terms of learning styles. This research is a quasi-experimental research using 2x3 factorial design. The respondents taken is the second semester students majoring in informatics engineering at the STMIK STIKOM Indonesia campus. The sampling procedure in this study was a random sampling technique that was started by carrying out the equivalency test of 4 classes taken using the one-way ANOVA test. After that randomly selected, two classes as an experimental class and two classes as a control class. To get instruments that have validity before use, questionnaires and tests are first tested and validated by experts who are experts in their fields. Normality and homogeneity tests are needed as a prerequisite before analyzing the data. The method used to analyze data is two-way ANOVA. The results showed that (1) student mathematics learning outcomes taught with telegram-assisted blended learning strategies were better than conventional mathematics learning outcomes of students taught, (2) the effect of telegraph-assisted blended learning strategies on student mathematics learning outcomes in learning styles. Based on the results of the research that has been carried out, it is recommended that further researchers or educators be able to develop a blended learning strategy as a way to convey learning material so that they can pay more attention to the learning styles of each student and can develop telegrams with more attractive features so that the telegram becomes one of online application for learning media.